Empowering Special Minds: A Systematic Review of Government Support for Students with Disabilities in Tanzania - Yusuph Maulid Kambuga; Miraji Mgonja (Nurul Jadid University, 2023)
The scope of the study includes an analysis of the implementation of inclusive education policies for students with disabilities in Tanzania as well as the identification of barriers that affect their effectiveness. This study aims to explore the conditions of implementation of inclusive education policies and identify challenges in achieving sustainable education inclusion for students with disabilities in Tanzania. The methodical strategy used to find relevant documents published between 2004 and 2022 was powered by the publish or perish domain across many electronic databases, namely Google Scholar, Institutional Repositories, and ERIC. Nine documents out of 41 were selected for data mining and analysis after meeting inclusion and exclusion criteria. The results show that the government has implemented several policies and strategies, like the Education and Training Policy, the Persons with Disabilities Act, the Inclusive Education Strategy, and educational regulations and circulars reinforcing inclusive education and children with disabilities' rights to access education. In addition, the government has established inclusive schools and special needs education departments at the ministerial level to address the several needs of students with disabilities. The review also highlights several impediments to implementing inclusiveness in education by government initiatives. These impediments include insufficient funds, dilapidated and inaccessible infrastructure, the community stigma related to disability, inadequate specialised experts, and a lack of assistive technology in many conventional schools. The implication of this research is to provide a better understanding of the effectiveness of inclusive education policy implementation in Tanzania and highlight the barriers that need to be overcome to achieve sustainable education inclusion for students with disabilities.